2005
DOI: 10.2486/indhealth.43.516
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Weightings Based on Biodynamics of Fingers-Hand-Arm System

Abstract: The frequency weighting for assessing hand-transmitted vibration exposure is critical to obtaining a true dose-response relationship. Any valid weighting must have a solid theoretical foundation. The objectives of this study are to examine the biodynamic foundation for assessing the vibration exposure and to develop a set of biodynamic methods to formulate the frequency weightings for different anatomical locations of the fingers-hand-arm system. The vibration transmissibility measured on the fingers, hand, wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
3
28
1
Order By: Relevance
“…Hence, the inertial force due to the transmitted acceleration on the fingers should be directly correlated to the interface dynamic force. This hypothesis was supported from the study by Dong et al 55) . They also found that at lower frequencies, the transmissibility on the fingers was not correlated to the interface biodynamic force.…”
Section: Vibration Transmissibilitysupporting
confidence: 81%
See 2 more Smart Citations
“…Hence, the inertial force due to the transmitted acceleration on the fingers should be directly correlated to the interface dynamic force. This hypothesis was supported from the study by Dong et al 55) . They also found that at lower frequencies, the transmissibility on the fingers was not correlated to the interface biodynamic force.…”
Section: Vibration Transmissibilitysupporting
confidence: 81%
“…7. Dong et al 55) reported that the accelerations on the arm calculated using the TAB weightings were highly correlated to those calculated using the ISO weighting 7) . Another study 56) reported that the wrist sensorineural disorders were reasonably correlated to the ISO-weighted acceleration.…”
Section: Vibration Transmissibilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Acceleration magnitudes were weighted using the frequency weightings displayed in figure 1 (11): W h is the frequency weighting specified in ISO 5349-1 (2); W h-bl is the band-limiting component of W h (10); W hf is a frequency weighting based on biodynamic studies of finger vibration power absorption (12); and W hT is a frequency weighting based on a Japanese study of VWF prevalence in worker groups investigated from 1957-1977 (13 The results of tool rms acceleration measurements with the four alternative frequency weightings are reported in a previous study (5).…”
Section: Measurement and Evaluation Of Vibration Exposurementioning
confidence: 99%
“…However, recent experimental and epidemiological studies suggest that this weighting may underestimate the risk of injury associated with exposure to higher frequency vibration (1,2). The goal of this study was to use a rat-tail model to determine how exposure to higher frequency vibration (i.e., 62.5 -250 Hz) affects peripheral nerves and arteries.…”
Section: Introductionmentioning
confidence: 99%